ATRAKSI EKOWISATA: ANALISIS STRATEGI PENGEMBANGAN CURUG BANGKONG DI KABUPATEN KUNINGAN JAWA BARAT - Yan hardiansyah; Ety Setiawati (Journal of Tourism Destination and Attraction, 2021)
Tourism, especially ecotourism attractions in Kertawirama Village, which is administratively one of the villages in the Nusaherang District, Kuningan Regency, will be able to be an alternative to increase community-based economic growth, by involving all elements of society, for example Bumdes, Farmer Groups, Youth Organizations and Local Government. The development of Curug Bangkong as far as observations and using SWOT analysis found several errors in development activities, namely the development of accessibility and tourist facilities that have the potential to cause environmental damage. One of them is physical development in ecotourism attractions. Visitors have not received sufficient information about the concept of ecotourism attractions which must be fully responsible for environmental conservation. Good ecotourism management should maximize the participation of local communities in managing Curug Bangkong, which in this case is represented by the Tourism Activating Group, Bumdes, Karang Taruna and PKK. It's just that it hasn't been felt optimal, because there are still many obstacles in its management. In data collection the methods used were literary studies, field observations and interviews with the village government. Analysis of data through qualitative methods with qualitative descriptive analysis methods. The results of the analysis are expected to be input for administrators in determining the appropriate development strategy for Curug Bangkong as one of the Ecotourism attractions in Kertawirama Village, Nusaherang District, Kuningan Regency, West Java Province.